Evaluation of tackling biomechanics in rugby: Video incident analysis and experimental set up - Seminati, E.; Cazzola, D.; Preatoni, E.; Trewartha, G. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
This study consisted of a video incident analysis of rugby tackles leading to spinal injuries, where players` behaviours and observed loading mechanisms were coded for each incident. The key features of these events were summarised, revealing the role of highspeed impacts, illegal tackles, and poor tackle technique in injury-causing tackles. In addition, lateral bending moments and lateral flexion movements were more prevalent than suggested by previous research. This investigation informed an experimental protocol for the analysis of simulated rugby tackles, with the final goal to obtain measures of cervical spine biomechanics during tackles. Data captured from this protocol could also be input into a full-body musculoskeletal model to provide descriptions of internal cervical spine loading in different tackle event scenarios.